Association between perioperative beta blocker use and cancer survival following surgical resection. Issue 8 (August 2018) - Musselman, Reilly P.; Bennett, Sean; Li, Wenbin; Mamdani, Muhammad; Gomes, Tara; van Walraven, Carl; Boushey, Robin; Al-Obeed, Omar; Al-Omran, Mohammed; Auer, Rebecca C.
Abstract: Background: Recent studies have demonstrated an association between beta-blocker exposure and improved survival in multiple cancer types. We sought to investigate the effects of beta-blockers at the time of index surgery for breast, lung, and colorectal cancer. Materials and methods: Using linked data from a provincial cancer registry, we conducted a retrospective matched cohort study comparing disease-specific and overall survival between patients over age 64 exposed and not exposed to beta-blockers before and after index surgical resection for breast, lung and colorectal cancer between April 1st, 2002 and December 31st, 2010. A high-dimensional propensity score was used to match patients and Cox proportional hazard models were used to estimate relative risks of the outcomes. Results: 30, 020 patients were included in the final matched cohorts. Mean follow up time for breast, lung, and colorectal cancer was 57.6 ± 30.5, 43.1 ± 28.7, and 53.4 ± 31.0 months, respectively. The adjusted hazard ratio for disease-specific mortality for patients exposed to beta-blockers was 1.03 (0.83–1.29) for breast, 1.05 (0.92–1.20) for lung, and 1.10 (0.96–1.25) for the colorectal cancer cohort. Conclusions: In this large population-based study, no association between perioperative beta-blocker exposure and improved cancer-specific survival for breast, lung, or colorectal cancer was demonstrated.